2010
DOI: 10.1016/j.pain.2010.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and beliefs among a community cohort with and without chronic low back pain

Abstract: Health literacy, the ability to seek, understand and utilise health information, is important for good health. Suboptimal health literacy has been associated with poorer health outcomes in many chronic conditions although this has not been studied in chronic low back pain (CLBP). We examined the health literacy of individuals with CLBP using a mixed methods approach. One-hundred and seventeen adults, comprising 61 with no history of CLBP and 56 with CLBP (28 with low and high disability, respectively, as deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
183
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(204 citation statements)
references
References 62 publications
18
183
1
2
Order By: Relevance
“…31 Patients filter, interpret, and remember information at the level of their understanding and in the context of their preexisting beliefs and motives. The data are, however, entirely consistent with what health care professionals report providing, 13,32 people with low back pain report receiving, 14,15 and direct consultation observations. 33 Regardless of participants' recall and bias, the messages that have stayed with them are probably more important than what was actually said or intended.…”
Section: Limitationssupporting
confidence: 77%
See 2 more Smart Citations
“…31 Patients filter, interpret, and remember information at the level of their understanding and in the context of their preexisting beliefs and motives. The data are, however, entirely consistent with what health care professionals report providing, 13,32 people with low back pain report receiving, 14,15 and direct consultation observations. 33 Regardless of participants' recall and bias, the messages that have stayed with them are probably more important than what was actually said or intended.…”
Section: Limitationssupporting
confidence: 77%
“…10,12,13 People with low back pain receive information from a range of sources, but the influence of each source is unknown. 14,15 Studies have investigated activities, situations, and anatomic structures that people see as being responsible for their back pain, but not how or why beliefs have been formed. 14,[16][17][18] Health care professionals may negatively influence patient beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most people experience some form of LBP at some point in their lives, a diagnosis for the pain experience can infrequently be determined on the basis of a spinal structural disorder [3]. Consequently, most LBP episodes are diagnostically classified as 'non specific LBP' and this remains a source of frustration for patients [4] trying to understand their problem and uncertainty for clinicians developing treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…Fear avoidance may lead to interference in activities of daily living (ADL) and may play an active role in the transition from acute to chronic pain [13,14]. It has been demonstrated that fear-avoidance beliefs were linked to the degree of disability, and that those with higher fear-avoidance beliefs have a higher level of disability [15]. Another study recommended that fear avoidance beliefs need to be considered in the management of pain and disability caused by LBP [16].…”
Section: Research Syamala Buragaddamentioning
confidence: 99%